Statement complementing the EFSA Scientific Opinion on application (EFSA‐GMO‐NL‐2010‐85) for authorisation of food and feed containing, consisting of and produced from genetically modified soybean MON 87769 × MON 89788. (12th May 2021) - ,; Naegeli, Hanspeter; Bresson, Jean Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: The European Commission mandated EFSA to complement its original scientific opinion on soybean MON 87769 × MON 89788 (EFSA‐GMO‐NL‐2010‐85) considering additional information on the human nutritional assessment of refined bleached deodorised oil produced from the two‐event stack soybean (RBD GM‐oil). The assessment was mainly based on a replacement scenario with a list of target foods where RBD GM‐oil is intended to be added. Intake estimations for several fatty acids present in the RBD GM‐oil, in particular γ‐linolenic acid (GLA), stearidonic acid (SDA) and linoleic acid (LA) were based on the consumption of the corresponding foods that are likely to be displaced. The assessment of LA considered the established adequate intake of 4% of total energy intake (E%) and that LA deficiency has not been observed with intakes > 1 E%. The assessment of GLA and SDA was conducted using maximum doses without adverse effects from intervention human studies as reference (4.2 grams/day for SDA and 2.8 grams/day for GLA) since no tolerable upper intake levels are set for these fatty acids. The decrease observed in the levels of LA in RBD GM‐oil as compared to oil from conventional soybean does not represent a nutritional concern as intakes were in all cases above 1 E%. For GLA, all intake estimations were below the reference dose indicating no safety concern. SDA intake estimations do not pose any safety concerns based on the overly conservative nature of the estimates, the absence of toxicological hazards and the rapid metabolism of SDA in humans. The GMO Panel concluded that the consumption of soybean MON 87769 × MON 89788 and their derived products, in particular its RBD oil, does not represent a nutritional concern in humans. A post‐market monitoring plan is recommended to confirm the predicted consumption and the application of conditions of uses considered during the pre‐market risk assessment.